2017
DOI: 10.1080/10871209.2017.1263768
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Illegal Bear Trade in Myanmar Through Conversations With Poachers: Topology, Perceptions, and Trade Links to China

Abstract: Myanmar is home to Asiatic black bears and sun bears. We gained insight into their hunting and trade in and out of Myanmar through conversations with 40 self-declared bear poachers. All respondents were male who killed or caught typically one to three bears a year, mostly by setting snares. There was a preference for Asiatic black bear. The perception was that bears were less abundant now than five years ago, but it was not more arduous to obtain one. Most poachers (75%) would consume the less valuable parts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…Kritik an der Verwendung von Wildtieren in der TCM, insbesondere von seltenen und geschützten Arten, ist kein neues Phänomen, gilt sie doch neben dem Konsum von Tieren für den Verzehr als größte Gefahr für die Artenvielfalt in China und immer mehr umliegenden Ländern, die Wildtiere nach China liefern ( EIA 2020a , b ; Nijman et al 2017 ; Zhang et al 2008 ; von Moltke & Spaninks 2000 ; Mainka & Mills 1995 ). Alleine auf dem TCM-Markt in Taiwan werden jährlich fast 200 Tonnen Schildkrötenpanzer verkauft, was Millionen getöteter Tiere entspricht ( Chen et al 2009 ).…”
Section: Einführungunclassified
See 1 more Smart Citation
“…Kritik an der Verwendung von Wildtieren in der TCM, insbesondere von seltenen und geschützten Arten, ist kein neues Phänomen, gilt sie doch neben dem Konsum von Tieren für den Verzehr als größte Gefahr für die Artenvielfalt in China und immer mehr umliegenden Ländern, die Wildtiere nach China liefern ( EIA 2020a , b ; Nijman et al 2017 ; Zhang et al 2008 ; von Moltke & Spaninks 2000 ; Mainka & Mills 1995 ). Alleine auf dem TCM-Markt in Taiwan werden jährlich fast 200 Tonnen Schildkrötenpanzer verkauft, was Millionen getöteter Tiere entspricht ( Chen et al 2009 ).…”
Section: Einführungunclassified
“…Bärengalle beinhaltet (s. Tabelle 1 ): Zum einen ist nun ein erneuter Anstieg der Wilderei auf wilde Bären in China wie auch in anderen asiatischen Ländern zu befürchten ( EIA 2020a ; Embury-Dennis 2020 ; Gomez 2020 ); betroffen sind hiervon v.a. Malaienbär ( Helarctos malayanus ) und Kragenbär ( Ursus thibetanus ) — beide Arten sind auf der Internationalen Roten Liste als gefährdet eingestuft, die Wilderei für die TCM ist einer der Gründe dafür ( Nijman et al 2017 ; Scotson et al 2017 ; Garshelis & Steinmetz 2016 ). Zum anderen erschwert diese Empfehlung alle Versuche, die auch aus Tierschutzgründen hochproblematische Haltung von bis zu 12.000 „Gallenbären“ auf Bärenfarmen in China und Vietnam zu beenden.…”
Section: Die Corona-pandemie Und Aktuelle Maßnahmen Der Chinesischeunclassified
“…The demand for bear parts in traditional medicines, i.e., gallbladders and bile, is particularly significant in China and Vietnam (Mills and Servheen 1994;Shepherd and Nijman 2007;Foley et al 2011;Burgess et al 2014;Davis et al 2016;Willcox et al 2016;Gomez and Shepherd 2018). This demand has been the reported cause for bear declines in Cambodia, Lao PDR, Myanmar and Vietnam (Nijman et al 2017;Crudge et al 2018). China and Vietnam are also the major sources of processed bear bile medicines, and regardless of policies in place that prohibit the international export of these products, medicines manufactured in both China and Vietnam have been observed illegally for sale in other countries in Asia (Foley et al 2011;Burgess et al 2014;Gomez and Shepherd 2018) as well as the USA and Canada (WAP 2020).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The illegal trade of bears in Asia has been well documented including the international trafficking of bears from Asia to other parts of the world (Foley et al 2011;Burgess et al 2014;Willcox et al 2016;Nijman et al 2017;Crudge et al 2018;Gomez and Shepherd 2018;Gomez and Shepherd 2019). While we know the trade in bears is prevalent outside of Asia, it remains poorly understood in terms of its extent, legality as well as trade dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Scotson et al (2014) showed that many plantation workers and owners did not mind sun bears in their plantations, because they could then opportunistically kill bears and sell their organs and other bear parts. In almost all countries throughout their range, adult sun bears are killed and used in traditional Asian medicine or sold for meat (Nijman et al 2017). Sun bear cubs are commercially traded as pets (Rog et al 2015).…”
Section: Introductionmentioning
confidence: 99%